The protective role of the alcoholic extract crude of the Plantago ovata plant seed compared with zinc against the toxicity of cadmium chloride on some biochemical and histological parameters in the male reproductive system of the white rat - Mohammed Shwish Saleh; Qasim Azeez Razooqi (Tikrit Journal of Pure Science)
This study was designed to find out the protective role of the alcohol Extract crude of plantago ovata compared to zinc, on some functional and histological criteria in male rats treated with cadmium chloride. The study was conducted in the animal house of Tikrit University / College of Veterinary Medicine for 30 days, 35 male white rats were used which were randomly divided into seven groups (5 animals per group). It was observed that the treatment of rats with CdCl2 resulted in a significant decrease (P≤0.01) in the SSH, ICSH and testosterone hormones compared to the control group, while the dose of rats treated with cadmium chloride with the ethanol extract of plantago ovata  seeds and the food supplement resulted in significant increases in the concentration of SSH hormones, ICSH And testosterone compared to treatment with cadmium chloride, Likewise, when healthy rats are dosed with the ethanol extract of plantago ovata seeds and zinc, we notice a significant increase in SSH, ICSH, and testosterone compared to control. The study showed that the treatment of rats with cadmium chloride and that a clear negative tissue change in the testes was represented by the destruction of the basal membrane of the seminal tubules and a small number of sperm cells, The dose of rats treated with CdCl2 with extract and zinc resulted in a clear histological improvement.